Advanced Electron Holography Applied to Electromagnetic Field Study in Materials Science. Issue 25 (17th November 2016) - Shindo, Daisuke; Tanigaki, Toshiaki; Park, Hyun Soon
Abstract : Advances and applications of electron holography to the study of electromagnetic fields in various functional materials are presented. In particular, the development of split‐illumination electron holography, which introduces a biprism in the illumination system of a holography electron microscope, enables highly accurate observations of electromagnetic fields and the expansion of the observable area. First, the charge distributions on insulating materials were studied by using split‐illumination electron holography and including a mask in the illumination system. Second, the three‐dimensional spin configurations of skyrmion lattices in a helimagnet were visualized by using a high‐voltage holography electron microscope. Third, the pinning of the magnetic flux lines in a high‐temperature superconductor YBa2 Cu3 O7−y was analyzed by combining electron holography and scanning ion microscopy. Finally, the dynamic accumulation and collective motions of electrons around insulating biomaterial surfaces were observed by utilizing the amplitude reconstruction processes of electron holography. Abstract : Advances and applications of electron holography to the study of electromagnetic fields in various functional materials are presented. In particular, the development of split‐illumination electron holography, which introduces a biprism in the illumination system of a holography electron microscope, enables highly accurate observations of electromagnetic fields and the expansion of the observable area.